Weight outcomes of NU-HOME: a randomized controlled trial to prevent obesity among rural children - Jayne A. Fulkerson; Melissa Horning; Daheia J. Barr-Anderson; Abbey Sidebottom; Jennifer A. Linde; Rebecca Lindberg; Sarah Friend; Jennifer Beaudette; Colleen Flattum; Rebecca L. Freese (BMC, 2022)
Abstract Background Rural children are at greater obesity risk than their urban peers. The NU-HOME study is an innovative collaborative effort to prevent childhood obesity in rural communities. Weight outcomes of the NU-HOME study, a family-meal focused randomized controlled trial (RCT) are described. We hypothesized that compared to control group children, intervention group children would have significantly lower weight-related post-intervention (PI) outcomes. Methods Participants were 114 dyads (7-10 year-old rural children and a parent). In 2017-2018 and 2018-2019, research staff measured height, weight and body fat at baseline (BL) and PI. Families were randomized to intervention (n = 58) or control (n = 56) groups without blinding. Designed with Social Cognitive Theory and community engagement, the NU-HOME program included seven monthly sessions delivered in community settings and four goal-setting calls. The program engaged entire families to improve healthy eating, physical activity, family meals and the home food environment. Multiple linear and logistic regression models tested PI outcomes of child BMIz-score, percent body fat, percent over 50th percentile BMI, and overweight/obesity status by treatment group, adjusted for BL values and demographics (n = 102). Results No statistically significant intervention effects were seen for child BMIz or overweight/obesity status. However, a promising reduction in boys' percent body fat (− 2.1, 95% CI [− 4.84, 0.63]) was associated with the intervention. Conclusions Although our findings were in the hypothesized direction, making significant impacts on weight-related outcomes remains challenging in community trials. Comprehensive family-focused programming may require intensive multi-pronged interventions to mitigate complex factors associated with excess weight gain. Clinical trial registration This study is registered with NIH ClinicalTrials.gov: NCT02973815 .